The complete mitochondrial genome of the Chinese rhesus macaques, Macaca mulatta lasiota. (2nd January 2016) - Wu, An-Quan; Ma, Ke-Shi; Yang, Tong-Wen; Sheng, Dong-Feng; Chen, Long; Li, Li-Li; Li, Cheng-Wei
Abstract: In this study, the complete mitochondrial genome sequence of the Chinese rhesus macaques Macaca mulatta lasiota has been reported for the first time. The total length of the mitogenome was 16, 561 bp. It contained the typical structure, including 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes and 1 control region. The overall composition of the mitogenome was A (31.7%), G (12.8%), C (30.4%) and T (25.1%). The M. mulatta lasiota mitogenome had 21 tRNA genes folded into a typical clover-leaf secondary structure except for tRNA Ser .